Space curves: Curvature and torsion - Velez, Ma. Milagros A. (Animo Repository, 1976)
This paper deals particularly with the problem in Metric Differential Geometry of proving the existence of a curve with a well defined curvature and torsion. The topic is a preliminary to the Theory of Surfaces which is useful in the fields of physics, surveying and navigation. It discusses theorems and proofs such as the following fundamental theorem: Let k(s) 0 and t(s) be defined in I = & s: 0 s r . If k(s) and t(s) are continuous functions on I, then there exists a curve C: r